Early clinical findings may predict long-term development of radiographic knee osteoarthritis in patients with anterior cruciate ligament reconstruction - Øiestad, Britt Elin; Chu, Constance R. (Annals of Joint, 2018)
The ideal consultation for a patient with anterior cruciate ligament (ACL) injury is when he or she receives evidence-based advice and information regarding future knee function and knee health—both short and long term—for different treatment options.